Design, Synthesis and Biological Evaluation of Ferrocenyl Thiazole and Thiazolo[5,4- D]Thiazole Catechols as Inhibitors of 5-Hlox and as Antibacterials Against Staphylococcus Aureus. Structural Relationship and Computational Studies - Vasquez-Martinez, y; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Cortez-San Martin, M; Gomez-San Martin, A; Gomez-San Martin, A; Muñoz-Osses, M; Muñoz-Osses, M; Flores-Vergara, E; Flores-Vergara, E; Torrent-Farias, C (American Chemical Society, 2020)
In the search for new human 5-lipoxygenase (5-hLOX) inhibitors that could be used for the treatment of a variety of inflammation-related diseases, three new ferrocenyl complexes derived from 2,4-thiazole and thiazolo[5,4-d]thiazole ((η5-C5H4-2,4-thiazol-3,4-dihydroxyphenyl)Fe(η5-C5H5) (3), (η5-C5H4-2,4-thiazol-phenyl)Fe(η5-C5H5) (4), and (η5-C5H4-thiazolo[5,4-d]thiazole-3,4-dihydroxybenzene)Fe(η5-C5H5) (5)) were synthesized and evaluated. A cooperative effect among the ferrocenyl, thiazole, and catechol fragments was evidenced and corroborated on evaluating the activity of the ferrocenyl (1) and catechol (2) precursors and additionally the organic derivative 6, similar to the NDGA structure. The thiazole derivative 3 was the best 5-hLOX inhibitor (85.8% inhibition, IC50 = 0.9 ± 0.7 μM for 5-hLOX and 22 ± 1.1 μM in human cells), followed by complex 4 (74.6% inhibition, IC50 = 5.4 ± 1.7 μM), which presents low cytotoxicity (>250 μM), associated with the absence of OH groups (decrease in reactive oxygen species generation). Molecular dynamic and docking studies of 3 and 4 showed that the ferrocenyl fragment is oriented to the active iron(III) site present in 5-hLOX; kinetics and FRAP assays together with electrochemical analysis suggest a redox mechanism mediated by water (Fe(III) from enzyme/Fe(II) from complex) accompanied by the blocking of the substrate approach, being consistent with competitive inhibition. The ferrocenyl, together with the thiazole and catechol fragments, drastically improves the antibacterial activity (percentage of bacterial growth inhibition of 85.5% and a MIC value of 25 μg/mL for 3), and an ROS assay suggests another mechanism for the antibacterial activity for Staphylococcus aureus. © 2020 American Chemical Society.